Enhancing the thermotolerance and erythritol production of Yarrowia lipolytica by introducing heat-resistant devices - Liang, Peixin; Li, Jing; Wang, Qinhong; Dai, Zongjie (Frontiers in Bioengineering and Biotechnology, 2023)
Yarrowia lipolytica has been widely used in the food biotech-related industry, where it plays the host's role in producing erythritol. Nevertheless, a temperature of about 28-30 °C has been estimated as the yeast's optimal growth temperature, leading to the consumption of a considerable quantity of cooling water, especially in summer, which is obligatory for fermentation. Herein is described a method for improving the thermotolerance and erythritol production efficiency at high temperatures of Y. lipolytica. Through screening and testing different heat resistant devices, eight refactored engineered strains showed better growth at higher temperature and the antioxidant properties of the eight engineered strains were also improved. In addition, the erythritol titer, yield and productivity of the strain FOS11-Ctt1 represented the best among the eight strains, reaching at 39.25 g/L, 0.348 g/g glucose, and 0.55 g/L/h respectively, which were increased by 156%, 86% and 161% compared with the control strain, respectively. This study provides insight into an effective heat-resistant device that could enhance the thermotolerance and erythritol production of Y. lipolytica, which might be considered a valued scientific reference for other resistant strains' construction.